THE MAIN DIRECTIONS OF ENSURING FOOD SECURITY IN THE DEVELOPMENT OF FAT AND OIL INDUSTRY - Abdukhakim Abdukarimovych, Yuldashev (Journal of process management and new technologies, 2018)
This article is devoted to the priorities of the development of the oil-and-gas industry of the Republic of Uzbekistan and its role in the economy of the country, sustainable development of the production of raw materials and oil-and-fat products, and measures to ensure food security in the oil and fat industry. Providing the population with quality foodstuffs, especially with ecologically clean vegetable oils, which are rich in various vitamins and human organisms, as well as achieving the "Fat-free independence" in the republic and increasing the productivity of surplus goods, by introducing free currency earnings orientation to socio-economic life of the country. If the amount of soybean production increases in the country, we will be stepping forward to provide food security through poultry and beef and meat products not only from oilseed oils and shrimp. The author provides for food security in the republic, filling the domestic market with high quality fat-and-oil products, modernization of oil and fat industry, launching new capacities, increasing the quality and productivity of oil-bearing plants, is one of the pressing issues, with the reduction of imports and increasing export volumes.